Posture Analysis With Rapid Upper Limb Assessment (RULA) Method at Students of Three Study Programs in Sari Mulia University - Madschen SMOSS Tambun; Agustina Hotma Uli Tumanggor; Husda Oktaviannoor (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
The spread of COVID-19 cases is taking place in a very fast time so that it has an impact on all sectors. One of the sectors affected is educational institutions. To prevent the spread of COVID-19 cases, all learning processes are carried out with an online learning system. Online learning causes an increase in sitting activities rather than standing activities, specially activity in front of a smartphone or laptop. Sitting activities that last for a long period of time can result in ergonomic risks. The purpose of the study was to analyze posture using the RULA method. Research was conducted on students of three study programs, namely Industrial Engineering, DIV-Health Promotion and Management with respondents 53 people. This study was conducted with a survey to see the posture of students when attending online lectures. From the results of the study obtained that the posture of students with RULA worksheet is in the range of 4 to 7. For rula score is mostly at a score of 6 as many as 24 students (45.28%). For RULA scores with scores of 5 and 7 as many as 10 people (18.86%). And rula score at a value of 4 as many as 9 people (16.98%).